Cataract Incidence in Sub-Saharan Africa: What does Mathematical Modeling tell us about Geographic Variations and Surgical Needs?. (October 2013) - Lewallen, Susan; Courtright, Paul; Etya'ale, Daniel; Mathenge, Wanjiku; Schmidt, Elena; Oye, Joseph; Clark, Anne; Williams, Talithia
Abstract Purpose: To apply a previously described mathematical model, designed to estimate cataract incidence from age-specific prevalence, to Rapid Assess of Avoidable Blindness survey data from Sub-Saharan Africa in order to estimate the incidence of cataract and therefore surgical needs. Methods: All Rapid Assessment of Avoidable Blindness surveys from Sub-Saharan Africa were identified. A previously developed mathematical model, designed to estimate the incidence of operable cataract was applied to those (27/32) meeting the inclusion criteria. Results: Incidence varied significantly across the continent with the result that cataract surgery rate targets required to eliminate cataract vary too. When variation in age structure is also taken into account, the cataract surgery rate needed to eliminate cataract visual impairment at the level of 6/18 ranges from 1200–4500 surgeries per year per million population. Conclusions: This is important evidence of significant variation in the incidence of cataract within Sub-Saharan Africa. The variation may be related to genetic or cultural variations on the continent and has important implications for planning services.